3D printed dielectric lens for the gain enhancement of a broadband antenna. Issue 4 (13th January 2020) - Anwar, Muhammad S.; Abufanas, Hasan; Bangert, Axel
Abstract: A novel 3D printed dielectric lens to enhance antenna gain parameters is presented. The lens is fabricated using a fused deposition method (FDM) which is a cost‐effective and an efficient 3D printing technique. Poly‐methyl methacrylate (PMMA) is used as a dielectric material due to its good RF properties. The thickness of the dielectric lens is 14 mm and provides a gain enhancement of up to 6.9 dBi over a wide frequency range. The dielectric lens is designed and computationally analyzed to demonstrate refractive index value close to zero. It has been shown that impedance‐matched near‐zero refractive index lens geometry eliminates strong reflections, and consequently enhances the antenna gain. A correlation is established between the individually, stacked unit cell layers and near‐zero refractive index cut‐off frequencies. The claim is substantiated through measured results using a broadband Vivaldi antenna. A gain enhancement of up to 6.9 dBi is recorded for the bandwidth from 13.5 to 24 GHz. An excellent correlation is reported between the measured and simulated results.